Anaerobic soil disinfestation: a biologically-based solution for sustainable crop production - Meshram, Shweta; Philbrick, Ashley N.; Adhikari, Tika B. (Frontiers in Horticulture, 2024)
Anaerobic soil disinfestation (ASD) is a novel, eco-friendly method to improve soil health. This method creates oxygen-free conditions by adding organic amendments as a carbon source, saturating the soil to field capacity, and then covering it with plastic. These anaerobic conditions reduce soilborne pathogens, enhance microbial diversity, and increase crop productivity. This review provides an overview of the different organic amendments used in ASD, their impact on managing soilborne pathogens, the role of beneficial microbiomes, and the challenges associated with adopting ASD. It also emphasizes the potential benefits of ASD and the innovative approach to advancing it for sustainable agriculture.